2005
DOI: 10.1007/s11089-005-6184-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Patterns Among Roman Catholic Clergy Accused of Sexual Misconduct

Abstract: A remarkable amount of international attention has focused on the sexual misconduct by Roman Catholic clergy in recent years. While the demographics and risk factor profiles of clergy sex offenders is now fairly well established, the psychological and personality profiles of these men are not. Very few empirical research studies have been published on the psychological and personality functioning of clergy who engage in sexual misconduct in the Catholic Church. The purpose of this study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 4 publications
2
31
0
1
Order By: Relevance
“…Specifically, 2% are believed to be potentially diagnosable as a pedophile (i.e., sexual focus on prepubescent children), while 4% could be diagnosable as an ephebophile (i.e., sexual fixation on those between the ages of 15 and 19 years of age) (Sipe 1990(Sipe , 1995. Other psychological issues that have been attributed to priests that have been known to engage in child sexual abuse include addiction, depression, and even cognitive dysfunction (Blanchard 1991;Plante and Aldridge 2005).…”
Section: Clergy Offender Characteristicsmentioning
confidence: 99%
“…Specifically, 2% are believed to be potentially diagnosable as a pedophile (i.e., sexual focus on prepubescent children), while 4% could be diagnosable as an ephebophile (i.e., sexual fixation on those between the ages of 15 and 19 years of age) (Sipe 1990(Sipe , 1995. Other psychological issues that have been attributed to priests that have been known to engage in child sexual abuse include addiction, depression, and even cognitive dysfunction (Blanchard 1991;Plante and Aldridge 2005).…”
Section: Clergy Offender Characteristicsmentioning
confidence: 99%
“…Perpetrators must also cope with their wrongdoings to some degree, which might include defensive responses such as repression (PLANTE, ALDRIDGE, 2005).…”
Section: Moral Strugglementioning
confidence: 99%
“…A review of the literature found only several small‐scale studies that have examined factors that may be etiologically related to clergy offending (e.g., D'Alton, Guilfoyle, & Randall, ; Haywood, Kravitz, Wasyliw, Goldberg, & Cavanaugh, ; Falkenhain, Duckro, Hughes, Rossetti, & Gfeller, ; Langevin, Curnoe, & Bain, ; Plante & Aldridge, ; Ukeritis, ). For example, Haywood and colleagues () found that the odds of a sexually abused cleric offending (as an adult) against children were 6.05 times higher than the odds of a non‐abused cleric becoming a child molester.…”
Section: Introductionmentioning
confidence: 99%